Optimising opioid substitution therapy in the prison environment. Issue 4 (5th December 2019) - Alam, Farrukh; Wright, Nat; Roberts, Paul; Dhadley, Sunny; Townley, Joanne; Webster, Russell
Abstract : Purpose: The purpose of this paper is to examine the current provision of opioid substitution therapy (OST) during and immediately following release from detention in prisons in England and Wales. Design/methodology/approach: A group of experts was convened to comment on current practices and to make recommendations for improving OST management in prison. Current practices were previously assessed using an online survey and a focus group with experience of OST in prison (Webster, 2017). Findings: Disruption to the management of addiction and reduced treatment choice for OST adversely influences adequate provision of OST in prison. A key concern was the routine diversion of opiate substitutes to other prisoners. The new controlled drug formulations were considered a positive development to ensure streamlined and efficient OST administration. The following patient populations were identified as having concerns beyond their opioid use, and therefore require additional considerations in prison: older people with comorbidities and complex treatment needs; women who have experienced trauma and have childcare issues; and those with existing mental health needs requiring effective understanding and treatment in prison. Originality/value: Integration of clinical and psychosocial services would enable a joint care plan to be tailored for each individual with opioid dependence and include options for detoxification or maintenance treatment. This would better enable those struggling with opioid use to make informed choices concerning their care during incarceration and for the period immediately following their release. Improvements in coordination of OST would facilitate inclusion of strategies to further streamline this process for the benefit of prisoners and prison staff.